Historical roots of personalism ideas in psychology - Stachowski, Ryszard (Studia Psychologica: Theoria et praxis, 2002)
The formation of scientific psychology during the 19th century was accompanied by the dilemma: on the one hand striving to establish exceptionless general rules, and on the other side universality of individual differences as perplexing exception to these rules. The author suggests that the appearance of personalism ideas in psychology, embodying the characteristics of “empirical necessity”, that directs investigations of general rules describing and explaining the way in which a person becomes unique, is a form of arbitrating the above presented dilemma.